Dolopteryx domestica Smithers (Psocoptera Psyllipsocidae) a new Psocoptera introduced in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
Dolopteryx domestica Smithers, species up to now found only in Rhodesia (now Zimbabwe), is noted in Italy.After showing the morphologic features which permit the exact classification, the female and male genitalia are described.Laboratory tests about insect's biology, proved that it is polyphagous, living on debris with a marked preference for starchy substrata.The most favourable temperatures for the growth range from 25 to 29°C, while at 18°C there is no eggs layering and insects survive only for few days.